Pengaruh Karakteristik Rumah Tangga terhadap Kejadian Kematian Maternal di Pulau Papua - Utami, Intan Putri; Wijaya, Yuliagnis Transver (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
Maternal health and life during pregnancy, childbirth, and the postpartum period are very important in determining the growth and future development of the birth generation. SDG indicators express the global seriousness of this effort, aiming to reduce the maternal mortality ratio (MMR) to less than 70 per 100,000 live births by 2030. However, according to the Long Form SP2020, Indonesia still has 189 deaths per 100,000 live births. Papua and West Papua are the two provinces with the worst MMR achievements, with 565 and 343 deaths per 100,000 live births, respectively. Therefore, this research will provide general overview and identify factors that influence the incidence of maternal mortality in households on Papua Island. The data is from Long Form SP2020 and is modeled using firth binary logistic regression. Variables that significantly influenced the incidence of maternal death in households on Papua Island were the classification area of residence, the number of household members, gender, age, education level, and the primary employment sector of the households head. The government needs to focusing maternal health programs on households that live in rural areas, are small households, have a head of household with low education, work in the agricultural sector, or are unemployed, and are older. Keywords: maternal mortality, Papua Island, firth logistic regression, Long Form SP2020